2021
DOI: 10.1007/s40964-021-00205-2
|View full text |Cite
|
Sign up to set email alerts
|

Review on additive hybrid- and multi-material-manufacturing of metals by powder bed fusion: state of technology and development potential

Abstract: In this review paper, the authors investigate the state of technology for hybrid- and multi-material (MM) manufacturing of metals utilizing additive manufacturing, in particular powder bed fusion processes. The study consists of three parts, covering the material combinations, the MM deposition devices, and the implications in the process chain. The material analysis is clustered into 2D- and 3D-MM approaches. Based on the reviewed literature, the most utilized material combination is steel-copper, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 70 publications
(68 reference statements)
1
31
0
Order By: Relevance
“…Upon visual inspection of the prototype components, all four nozzles were successfully manufactured. It can be concluded that the methods described in previous research for MM part generation utilizing PBF-LB/M can be applied to complex industrial applications [2,4,5,10,39].…”
Section: Method Materials and Component Manufacturingmentioning
confidence: 99%
See 4 more Smart Citations
“…Upon visual inspection of the prototype components, all four nozzles were successfully manufactured. It can be concluded that the methods described in previous research for MM part generation utilizing PBF-LB/M can be applied to complex industrial applications [2,4,5,10,39].…”
Section: Method Materials and Component Manufacturingmentioning
confidence: 99%
“…The build job was created from the CAD model. Therefore, separate models were derived for each material [2]. Thus, the steel body volume and the copper inlet volume were exported as STL files.…”
Section: Method Materials and Component Manufacturingmentioning
confidence: 99%
See 3 more Smart Citations